Pengaruh Profitability, Firm Size, Dan Earnings Persistence Terhadap Earnings Response Coefficient - Nicholas Eri Saputra, Rousilita Suhendah (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is obtain empirical evidence about effect of profitability, firm size, dan earnings persistence on earnings response coefficient in manufacturing companies listed on Indonesia Stock Exchange (IDX) for the 2017-2019 period. This research used 69 samples and 207 data from manufacturing companies selected by purposive sampling method. The data in this research were inputted and calculated using the Microsoft Excel program and process using the Eviews 11 program. The result of this research indicated that earnings persistence has a positive and significant effect on earnings response coefficient while profitability and  firm size have no significant effect on earnings response coefficient. The implication of this study is persistence profit will make investors more interested in investing.